1991
DOI: 10.1104/pp.97.2.523
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Invertase Deficiency in the Primary Root of an Inbred Maize Line

Abstract: An organ-specific invertase deficiency affecting only the primary root system is described in the Oh 43 inbred maize (Zea mays). Invertases (acid and neutral/soluble and insoluble) were assayed in various tissues of hybrid (NK 508) Sucrose breakdown is critical to the vast majority of plant species because nonphotosynthetic tissues depend on import ofthis sugar for their growth and development. Initial cleavage of sucrose can be catalyzed by either invertase (EC 3.2.1.26) or the reversible enzyme sucrose syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Koch et al (1992) found that, in intact maize roots, Suc synthase genes are strongly expressed in virtually a11 root tip cells except for columella cells of the cap, implying that substantial Suc metabolism occurs in the meristematic region. In addition, cell-wallbound invertase activity, which would be required for this transport mechanism, is highest in the apical 2 mm of the maize primary root, and has vanished by 8 mm from the tip (Duke et al, 1991).…”
Section: Alternative Mechanisms Of Transport: Symplasmic Possibilitiesmentioning
confidence: 99%
“…Koch et al (1992) found that, in intact maize roots, Suc synthase genes are strongly expressed in virtually a11 root tip cells except for columella cells of the cap, implying that substantial Suc metabolism occurs in the meristematic region. In addition, cell-wallbound invertase activity, which would be required for this transport mechanism, is highest in the apical 2 mm of the maize primary root, and has vanished by 8 mm from the tip (Duke et al, 1991).…”
Section: Alternative Mechanisms Of Transport: Symplasmic Possibilitiesmentioning
confidence: 99%
“…A vacuolar invertase path for Suc hydrolysis would be especially useful in a symplastically continuous system of phloem-unloading and post-phloem transport where internal Suc cleavage could sustain Suc gradients across plasmodesmata (Duke et al, 1991;Sturm et al, 1995;Fisher and Cash-Clark, 2000b;Kim et al, 2000). The abundant activity and mRNA localization in parenchyma surrounding terminal regions of vascular bundles in maize ovaries (Figs.…”
Section: Role Of Vacuolar Invertase In Young Ovariesmentioning
confidence: 99%
“…In organs that import sugar, Suc is converted to Glc by locally expressed Suc synthase or invertase (Koch, 2004). In root, for example, Suc invertase and synthase are expressed preferentially in the meristem and early elongation zone (Duke et al, 1991;Barratt et al, 2009). Consequently, sugar concentration is high in cells that are involved in uploading and downloading.…”
mentioning
confidence: 99%